Decoupling of the Occipitotemporal Cortex and the Brain's Default-Mode Network in Dyslexia and a Role for the Cingulate Cortex in Good Readers: A Brain Imaging Study of Brazilian Children. Issue 1 (2nd January 2019) - Buchweitz, Augusto; Costa, Adriana Corrêa; Toazza, Rudineia; de Moraes, Ana Bassôa; Cara, Valentina Metsavaht; Esper, Nathália Bianchini; Aguzzoli, Cristiano; Gregolim, Bruna; Dresch, Luiz Fernando; Soldatelli, Matheus Dorigatti; da Costa, Jaderson Costa; Portuguez, Mirna Wetters; et al.
ABSTRACT: The goal of the present study was to investigate intrinsic and reading-related brain function associated with dyslexia and typical readers in monolingual Brazilian children. Two fMRI studies were carried out: a resting-state and a word-reading study. The results show (a) underconnectivity between the occipitotemporal region (visual word form area) and the brain's default-mode network in dyslexic readers and (b) more activation of the anterior cingulate cortex for typical readers relative to dyslexic readers. The findings provide evidence for brain connectivity and function differences in an underrepresented population in fMRI studies of dyslexia; the results suggest atypical intrinsic function, and differences in directed attention processes in dyslexia.